Technology-Enhanced Feedback System Usability in the Context of Self-Regulation Promotion - Alenka Žerovnik (Education Sciences, 2024)
Numerous studies have explored the integration of technology-enhanced feedback systems in education. However, there is still a need for further investigation into their specific impact on teacher satisfaction, which is essential for effective feedback delivery to students. This study addresses this gap by analyzing teachers’ satisfaction with the “Compliments and Comments Tool”, a technology-enhanced system developed to provide written feedback to students. Using a quantitative approach, this study examined teachers’ perceptions of the tool’s usability in the Slovenian education context, involving a diverse group of 3412 primary and secondary school teachers. Data were collected through surveys employing the System Usability Scale (SUS) and Technology Acceptance Model (TAM) for quantitative analysis, complemented by qualitative insights. The results showed high teacher satisfaction, valuing the tool for facilitating feedback and supporting a positive learning environment. These findings suggest that the “Compliments and Comments Tool” is a valuable addition to educational technology, promoting effective teaching and enhancing student engagement. This study emphasizes the critical role of user-centered design and system usability in educational technology, particularly in fostering effective feedback and promoting student self-regulation.